The Innocent Defendant's Dilemma: An Innovative Empirical Study of Plea Bargaining's Innocence Problem - Dervan, Lucian E. (2013)
In this Article, Professors Dervan and Edkins discuss a recent psychological study they completed regarding plea bargaining and innocence. The study, involving dozens of college students and taking place over several months, revealed that more than half of the innocent participants were willing to falsely admit guilt in return for a benefit. These research findings bring significant new insights to the long-standing debate regarding the extent of plea bargaining’s innocence problem. The Article also discusses the history of bargained justice and examines the constitutional implications of the study’s results on plea bargaining, an institution the Supreme Court reluctantly approved of in 1970 in return for an assurance that it would not be used to induce innocent defendants to falsely admit guilt